Pengembangan Media Imajinasi Hiragana Berbasis Android Studio Sebagai Cara Cepat Untuk Menghafal Huruf Bahasa Jepang Pada Siswa Kelas X IPA - Yulia - Yusuf (Balai Diklat Keagamaan Surabaya, 2021)
The purpose of this research is to describe the process of developing an Android-based Imaginary Hiragana media, describe the quality of developing media and describe the effectiveness of using the Android-based Imaginary Hiragana media as a quick way to memorize Japanese letters. Based on the validation value of the material validator and graphic design that is equal to 76.29%, the product of this research development is good for use as a learning medium for memorizing Hiragana letters using imagination techniques. While the response or interest of students in learning Hiragana is in the positive category, this means that students of beginner Japanese language learners of class X Science show enthusiasm for learning Japanese. While the results of daily tests on